Seasonal estimates of densities and predation rates of cetaceans in the Ligurian Sea, northwestern Mediterranean Sea: an initial examination - Laran , Sophie; Joiris , Claude; Gannier , Alexandre; Kenney , Robert D. (J. Cetacean Res. Manage., 2023)
The Ligurian Sea is one of the most attractive areas for cetaceans in the Mediterranean Sea, and is now included in a Marine Protected Area, the Pelagos Sanctuary. Despite a lower species diversity than in other parts of the world, because of their abundance, cetaceans are thought to represent significant consumers in this ecosystem. Surveys were conducted within the Pelagos Sanctuary from 2001 to 2004. Densities of five species: striped dolphin (Stenella coeruleoalba); fin whale (Balaenoptera physalus); sperm whale (Physeter macrocephalus); long-finned pilot whale (Globicephala melas); and Risso’s dolphin (Grampus griseus), were estimated and converted to biomass. Total biomass density of cetaceans in the Ligurian Sea was estimated as 93kg km-2 (CV=28%) in winter (October to March) and 509kg km-2 (CV=16%) in summer (April to September). Daily predation rates by cetaceans were estimated as 2.9kg km-2 d-1 in winter, increasing to 10.4kg km-2 d-1 in summer, corresponding to a total annual ingestion of 2.4t km-2 y-1. The annual primary production required for cetaceans was estimated to be 12.6gC m-2 y-1, corresponding to 6- 15% of the net primary production known for this area. Estimated cetacean predation on fish was similar to reported fisheries landings, nevertheless, management of artisanal fisheries and accurate quantification of the resources they exploit will be necessary for the responsible management of fisheries in this Mediterranean Marine Protected Area.